Determinant of Employee Performance at Community Health Center: Exploring the Intervening Effect of Job Satisfaction - Eko Apriyanto; Sri Utami Ady; Nur Sayidah (Journal of Accounting and Finance Management, 2026)
Utilizing Partial Least Squares-Structural Equation Modeling (PLS-SEM), this study examines the structural relationships between work motivation, performance allowances, job satisfaction, and employee performance at community health centers in Surabaya. Based on survey data from 126 employees, the model demonstrates that motivation and performance-based incentives are significant predictors of both job satisfaction and performance. The analysis confirms the mediating role of job satisfaction within this framework. Consequently, the research recommends the development of robust motivation-driven policies and transparent benefit structures to achieve superior organizational performance.